From laboratory to clinic: opportunities and challenges of functional food active ingredients in cancer therapy - Zhang, Nie; Ren, Yanzhi; Xu, Yahui (Frontiers in Nutrition, 2025)
This review provides a comprehensive analysis of the potential of functional food active ingredients in cancer prevention and therapy. It outlines the multifaceted anticancer mechanisms of bioactive compounds—such as polyphenols, carotenoids, omega-3 fatty acids, phytosterols, alkaloids, isothiocyanates, polysaccharides, phenolic acids, flavonols, and amide-bearing compounds—which include antioxidant and anti-inflammatory activities, induction of apoptosis and autophagy, modulation of the tumor microenvironment, interference with cell cycle regulation and signaling pathways, and regulation of cancer-related microRNA expression. The review further discusses the synergistic effects of these compounds when combined with conventional treatments like radiotherapy and chemotherapy, highlighting their role in enhancing efficacy and mitigating side effects. Despite promising preclinical data, challenges such as poor bioavailability, dose-dependent safety concerns, and the need for large-scale randomized clinical trials and regulatory standardization remain. Proposed future directions include advanced nanodelivery systems, eutectic technologies, and precision nutrition strategies, which together could accelerate the translation of these natural compounds from the laboratory to clinical application. Ultimately, the integration of functional food active ingredients into comprehensive cancer care may offer novel, safer, and more personalized approaches to oncologic treatment and prevention.